Fluorescent polydopamine nanoparticles as a nanosensor for the sequential detection of mercury ions and l-ascorbic acid based on a coordination effect and redox reaction. Issue 47 (27th July 2020) - Yang, Yi-Xuan; Fang, Yan-Zhao; Tian, Jing-Xuan; Xiao, Qiang; Kong, Xiang-Juan
Abstract : A novel fluorescence nanosensor using intrinsic fluorescent polydopamine nanoparticles as an effective signal reporter was constructed for simple, rapid and sequential detection of Hg 2+ ions and l -ascorbic acid based on a coordination effect and redox reaction. Abstract : Herein, a novel fluorescence nanosensor using intrinsic fluorescent polydopamine nanoparticles (PDA NPs) as an effective signal reporter has been constructed for the simple, rapid and sequential detection of mercury ions (Hg 2+ ) and l -ascorbic acid (AA) based on a coordination effect and redox reaction. The fluorescence of the PDA NPs could be specifically quenched by Hg 2+ through intense coordination effects between the Hg 2+ and the groups (catechol, amine, ketone and imine) on the surface of the PDA NPs. However, when AA and Hg 2+ coexisted in solution, the fluorescence of the PDA NPs pronouncedly recovered via the redox reaction of Hg 2+, with it being reduced to Hg 0 by AA. The fluorescence quenching mechanism of Hg 2+ towards the PDA NPs and the redox reaction between Hg 2+ and AA were also fully investigated. The nanosensor exhibited high sensitivity and desirable selectivity for Hg 2+ and AA detection. Moreover, the strategy was successfully explored in real samples (tap water, lake water and human serum samples) with satisfactory recoveries. The developed nanosensor provides new sights and good inspiration for Hg 2+ and AA detection under real conditions.